Ericoid mycorrhizal growth response is influenced by host plant phylogeny - Neves, Alice S; van Galen, Laura G; Vohník, Martin; Peter, Martina; Martino, Elena; Crowther, Thomas W; Delavaux, Camille S (Mycorrhiza, 2025)
Ericoid mycorrhizal (ErM) fungi (ErMF) are crucial for the establishment of thousands of ericaceous species in heathlands and wetlands by increasing their tolerance to harsh conditions and improving nutrient uptake. However, ErM research has largely focused on a limited number of host species and four ErMF species (especially Hyaloscypha hepaticicola and Oidiodendron maius, to a lesser extent H. bicolor/H. finlandica and H. variabilis). Therefore, the degree to which other ericaceous plants and ErMF form functional associations, and corresponding benefits for plant growth, are not well understood. As such, we lack a clear understanding of how changes in fungal partners may influence plant fitness. To address this gap, we conducted a greenhouse experiment with nine ericaceous plant species and eight ErMF isolates to expand baseline knowledge regarding the effects of the ErM symbiosis on host plant growth. By analyzing ErM root colonization and host plant growth response, we observed that the mycorrhizal growth response (MGR) was variable and depended on plant and fungal identity. Moreover, overall inoculation effects on plant growth were independent from colonization levels. Finally, we found evidence that MGR was influenced by plant phylogeny. These results expand our basic understanding of the ErM symbiosis and provide valuable information for future restoration and conservation efforts.
Keywords: symbióza; Mycorrhizae; Ericoid mycorrhizal fungi; kořeny rostlin; Phylogeny; Plant Roots; Heathland; Wetland; Symbiosis; mykorhiza; fylogeneze; Ericaceae; Mycorrhizal growth response